Molecular mechanism of photosystem I assembly in oxygenic organisms - Yang, Huixia; Liu, Jun; Wen, Xiaogang; Lu, Congming (Biochimica et biophysica acta, 2015)
Photosystem I, an integral membrane and multi-subunit complex, catalyzes the oxidation of plastocyanin and the reduction of ferredoxin by absorbed light energy. Photosystem I participates in photosynthetic acclimation processes by being involved in cyclic electron transfer and state transitions for sustaining efficient photosynthesis. The photosystem I complex is highly conserved from cyanobacteria to higher plants and contains the light-harvesting complex and the reaction center complex. The assembly of the photosystem I complex is highly complicated and involves the concerted assembly of multiple subunits and hundreds of cofactors. A suite of regulatory factors for the assembly of photosystem I subunits and cofactors have been identified that constitute an integrative network regulating PSI accumulation. This review aims to discuss recent findings in the field relating to how the photosystem I complex is assembled in oxygenic organisms. This article is part of a Special Issue entitled: Chloroplast Biogenesis. •PSI is highly conserved in photosynthetic membranes.•Evolution of subunit composition and oligomeric state of PSI•Assembly factors for PSI subunits and cofactors•Cooperation of assembly factors for PSI assembly•Dynamic regulations of assembly factors for PSI assembly